PENGARUH SPORT SPONSORSHIP TERHADAP REPURCHASE INTENTION - Jonatan Jonatan; Theresia Dwinita Laksmidewi (Prosiding Working Papers Series In Management, 2018)
Sports are a very interesting activity to be sponsored for companies that have a target market in that field. The company participated directly with Indonesian futsal league event that attracted the fans of futsal by cooperating through sponsorship of big futsal team in Indonesia. This study examined the effect of Sport Sponsorship on Repurchase Intention of Futsal Product SPECS. The research method used survey on a sample of 150 respondents of Futsal player. Hypothesis testing using multiple regression. Result showed that personal liking for the event and attitude to the sponsor have effect on repurchase intention. Whereas perceived status of event, sponsor event fit, sincerity of sponsor and ubiquity of sponsor had no effect on repurchase intention.Keyword: Sport Sponsorship, Repurchase Intention